Transition to Online Learning: Implementing the TPACK Framework by English Teachers due to the COVID-19 Pandemic - Achmad Ivansyah Obos; Aridah Aridah; Desy Rusmawaty (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
The objectives of this research is to explore how the English teachers implement TPACK in online learning context and to know the challenges faced by the English teachers in implementing TPACK. There were several studies in the implementation of TPACK, but still less on the discussion about the challenges that the English teachers faced while implementing it, particularly in the online learning due to the COVID-19 pandemic. This study employed a descriptive design with a qualitative approach, which were analyzed descriptively through reducing inappropriate data, displaying and concluding data. The results of the data revealed that the English teachers of Bunga Bangsa Islamic Junior High School Samarinda had implemented TPACK in online learning context by using WhatsApp, Zoom meeting and Google Classroom as the technologies used to teaching, conducting demonstration and recitation method as the pedagogy to teach about “object pronoun” and “will and going to” as the content. There are some challenges faced by the English teachers when they implemented TPACK in online learning context such as limited quota, bad signal of internet, students’ behavior and adapt to the applications used such as WhatsApp, Zoom meeting and Google Classroom.